2002
DOI: 10.1289/ehp.02110427
|View full text |Cite
|
Sign up to set email alerts
|

Summary of the National Toxicology Program's report of the endocrine disruptors low-dose peer review.

Abstract: At the request of the U.S. Environmental Protection Agency (U.S. EPA), the National Toxicology Program organized an independent and open peer review to evaluate the scientific evidence on low-dose effects and nonmonotonic dose-response relationships for endocrine-disrupting chemicals in mammalian species. For this peer review, "low-dose effects" referred to biologic changes that occur in the range of human exposures or at doses lower than those typically used in the standard testing paradigm of the U.S. EPA fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
155
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(158 citation statements)
references
References 1 publication
1
155
0
2
Order By: Relevance
“…In fetuses and neonates, Taylor et al (2008) observed low levels of the enzyme that conjugate BPA (uridine diphosphate-glucuronosyl-transferase), implying that both oral and non-oral administration of BPA during neonatal life provide the same internal active dose. The EPA-National Toxicology Program's Report of the Endocrine Disruptors-USA (U.S.EPA 1993) has defined the LOAEL dose for BPA as 50 mg/kg per day and the 'safe dose' as 1000 times lower (50 mg/kg per day) (Melnick et al 2002, Shelby 2008. In this work, we used the safe dose of BPA and a dose 100 times lower.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…In fetuses and neonates, Taylor et al (2008) observed low levels of the enzyme that conjugate BPA (uridine diphosphate-glucuronosyl-transferase), implying that both oral and non-oral administration of BPA during neonatal life provide the same internal active dose. The EPA-National Toxicology Program's Report of the Endocrine Disruptors-USA (U.S.EPA 1993) has defined the LOAEL dose for BPA as 50 mg/kg per day and the 'safe dose' as 1000 times lower (50 mg/kg per day) (Melnick et al 2002, Shelby 2008. In this work, we used the safe dose of BPA and a dose 100 times lower.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…However, no histopathologic abnormalities were observed in young adulthood. Furthermore, the low-dose estrogenic response in the prostate gland has not been consistently reported (71), due in part to species/strain differences, background estrogen levels and other experimental variables, and is a matter of considerable debate (72,73). To examine this issue in the neonatal rat model, we administered estradiol over a 7-log range of doses on neonatal days 1, 3 and 5 in both Sprague-Dawley rats and the more estrogen-sensitive Fischer 344 rats (74).…”
Section: Neonatal Exposure To Low-dose Estradiol and Bisphenol Amentioning
confidence: 99%
“…Bisphenol A (BPA), another environmental estrogen and an endocrine disruptor, is a synthetic chemical primarily used to produce polycarbonate plastics and epoxy resins (Cooper et al, 2008;EC, 2003;Melnick et al, 2002). Due to the diverse uses of BPA in consumer products, it has been regularly detected in a wide range of environmental matrices, including air, water, sewage sludge and sediments (Huang et al, 2012;Lee et al, 2013;Xiong et al, 2015), even human blood and tissues (Vandenberg et al, 2010;Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%